THE IMPORTANCE PERFORMANCE ASSESSMENT AND ITS IMPACT ON IMPROVING PERFORMANCE OF PUBLIC SERVICE ORGANIZATIONS IN SOUTH TANGERANG CITY - Rahmat Salam (Universitas Padjadjaran, 2021)
So far, the performance appraisal of an organization is inaccurate because the assessment is only based on employee compliance with their superiors without providing an assessment based on the contribution made by the employee to the organization. This certainly impacts the employee’s weak motivation, so that it can affect organizational performance, which affects the quality of public services. This research tries to present the analysis of employee performance appraisal by emphasizing the determined qualities (competencies) to improve the performance of public service organizations in Indonesia. It can be seen that performance measurement can be used as a reference as a measure of the performance of an organization. The research was conducted using a literature review study. And use a qualitative approach in analyzing the data presented in the study. The study found that their direct superiors generally evaluate employees. Concerning the frequency of promotion in o organization, each leader explains that the organization has a clear pattern in determining the promotion and position. This is the authority of management. However, sometimes organizational leaders allow biased factors such as gender issues, appearance problems, specific ethnicity or race or feelings of hatred towards someone. Affect their judgment. Unless appraisals are based on actual job performance, they will continue to be conducted without the goals often required in fair performance appraisal systems.